Taking Stock, July 2019 : Recent Economic Developments of Vietnam - World Bank (World Bank, Washington, DC, 2019)
The external environment has deteriorated during the first half of 2019, and downside riskspredominate in the near-term. Global GDP growth is projected to decline to 2.6 percent in 2019 from 3 percent in 2018, reflecting broad-based weakness in advanced economies and major Emerging Market and Developing Economies. Reflecting slower growth and heightened policy uncertainty associated with protected trade tensions, global trade growth is protracted to weaken further from 4.1 percent in 2018 to 2.6 percent in 2019. Downside risks include a further escalation of trade disputes between the world's two largest trading nations, while a more pronounced downturn in global activity and increased volatility in financial flows. Amidst rising global headwinds, Vietnam's economic growth momentum has been slowing since the beginning of the year. Vietnam's real GDP growth has decelerated to a still robust 6.8 percent in the first quarter of 2019 from a vibrant 7.5 percent pace in the same period of 2018. Slower growth reflects several factors. Agricultural output decelerated due to the outbreak of African swine fever and a decline in international prices. Weaker external demand moderated growth of the export-oriented manufacturing sector as well as overall export performance, even though Vietnam seems to have benefitted from some trade diversion due to the ongoing trade tensions between China and the US. Domestic investment appears to be slowed resulting from subdued credit growth and continued consolidation in public investment. Other macroeconomic indicators, such as more sluggish credit growth, subdued inflation and slower import growth are further signs of a cyclical moderation in economic activity. In contrast, service sector activity continues relatively strong, signaling sustained buoyancy in private consumption. Despite a recent uptick in headline inflation, price pressures have remained subdued as credit growth moderated. The headline CPI rose by 2.9 percent (y/y) in May 2019, up slightly from 2.6 percent in January 2019, driven by hikes in administered prices (for electricity and fuel) and moderate food price increases. The State Bank of Vietnam maintained a prudent monetary policy stance to support its twin goals of sustaining macroeconomic stability and supporting overall economic growth. Credit growth is estimated to have slowed to about 13 percent (y/y) in March 2019 reflecting tighter credit policies.